Design and Implementation of Real-Time Health Vital Sign Monitoring Device with Wireless Sensor-based on Arduino Mega - Wulandari, Bekti; Jati, Mentari Putri (Elinvo (Electronics, Informatics, and Vocational Education), 2021)
This paper discusses the realization of vital sign monitoring devices and knowing their performance. This device is expected to assist medical personnel in measuring and monitoring vital signs without having to have physical contact with patients. The design phase of the patient's vital sign monitoring device with an Arduino Mega-based wireless sensor starts from the identification, needs analysis, design, manufacture, troubleshoot, and testing. Arduino Mega and ESP8266 as the main components that function for the controller and upload data to the server. Then MAX30100, DS18B20, and MPX5700AP sensors which function to detect the vital sign. Android smartphones are used to display measurement results in real-time, save and display vital sign data records. Based on the test results, the patient's vital signs monitoring device has an average difference of 0.67% for temperature checks, 1.19% for pulse checks, 0.77% for SPO2 examinations, 4.78%, and 8.91% for systolic and diastolic blood pressure examinations.